Work and non-work-related antecedents of expatriates' well-being : A meta-analysis - Biswas, Tania; Mäkelä, Liisa; Andresen, Maike (Elsevier, 2021)
Studies show a reduction in expatriates' well-being while abroad which entails a risk of low performance or even termination of the assignment abroad. To extend the knowledge of antecedents of expatriates' well-being, this meta-analytic review combines the empirical results from 24 studies. Concerning the conservation of resources theory, we distinguish between work-related and non-work-related antecedents (resources) and expose their relationship with expatriates' work well-being and general well-being. The meta-analysis shows that work well-being is positively anteceded by organizational support, work adjustment, and spousal support, whereas job factors and work-family interference are associated with decreased work well-being. General well-being negatively relates to work-family interference factors. The antecedents with the highest relative effect size are job factors on the negative side (resource loss) and organizational support on the positive side (resource gain). Work-family interference has the broadest impact on both work well-being and general well-being.
Keywords: expatriate; general well-being; meta-analysis; work well-being; fi=Henkilöstöjohtaminen|en=Human Resource Management|